The Implementation of Online-Designed Adult Learning in the Online Business School (SBO) - Deti Nudiati; Viena Rusmiati Hasanah; Tasbiah Siti Maesaroh; Rini Nuraeni; Krisnayanti Krisnayanti (Universitas Negeri Padang, 2023)
Since Indonesia was declared a pandemic, the majority of Skills and Training Institutions (STIs) have not been able to survive and have closed down. This is especially true for STIs that were designed for face-to-face learning and could not adapt to the change to digital-based learning. Meanwhile, the characteristics of adults who have various learning models, motivation, interests, and goals require individualization in learning, which is usually accommodated by face-to-face education. Therefore, this research aims to find out how the implementation of adult learning is carried out in non-formal education institutions, namely the Online Business School (SBO). This research uses a qualitative approach and descriptive method, with the aim of obtaining an overview of the implementation of adult education learning at the non-formal education unit, the Online Business School (SBO). The research findings show that as a training institution that had designed its training online long before the pandemic, SBO applies a learning model that is not much different from the training that has changed to online due to the social restrictions imposed by the Indonesian government. Nevertheless, the minimal implementation of adult learning still makes SBO an attractive program as indicated by an average of 50-60 learners and reaching its peak during the pandemic.